The effect of some technological aspects on the Coriandrum Sativum L. crop and fruit quantity - Ignat Evodia Sidonia; Gheorghe David (2013)
The researches were carried out on Timis Plain, Timişoara region, on a moderate gleyed molic eutricambosoil. According to Köppen the climate of the researched perimeter is framed into the climatic province c.f.b.x. The studied factors are the effect of using nitrogen fertilizers in variable doses on a constant base of P60K60 and the distance between rows and the density of seeding on the diachene crop as well as on the volatile oil production. As an average, the nitrogen fertilizers increased the crop by 36% for the fertilizer variant N30 and by 42%, for the fertilizer variant N60 in the researched perimeter. The optimal density is of 200 germinable seeds / m2. By increasing the density to 300 germinable seeds / m2 the crop results decreases with 4 %, and for the variant seeded with a density of 400 germinable seeds / m2 the crop decrease is of 15 %. The optimal distance between rows is 12.5 cm. The nitrogen fertilizers reduce the volatile oil content by 0.10 % to 0.20 %, but increase the volatile oil production with up to 6.5 kg/ha, as a result of the increase of the yield.
Keywords: Mezőgazdaság-tudományok; Mezőgazdaság, erdészet, halászat